Haematological responses of Australian owls to naturally occurring disease or injury - Clark, Phillip; Boardman, W.; Raidal, S. (Springer U K, 2013)
We investigated the haematological characteristics exhibited in response to a range of injuries and naturally occurring inflammatory disease, of 11 birds from five species of owls. A spectrum of haematological responses was observed. The PCV was between 0.32 and 0.56 l/l. The concentration of total leukocytes varied between each case, with the least concentration of 3.75×109/l and the greatest concentration of 17.03×109/l. Heterophils were the predominant leukocyte in 7/11 cases, lymphocytes were the predominant leukocyte in 3/11 cases and eosinophils the predominant leukocyte in 1/11 case. Morphological atypia of leukocytes was recognised in all cases. This study illustrates the heterogeneous haematological response exhibited by owls to naturally occurring disorders.